An exploration of revenge within romantic relationships - Dustagheer, Elspeth (2020)
Background: Following interpersonal transgressions, some individuals have difficulty letting go of hostile feelings towards their transgressor, foregoing forgiveness and enacting revenge. Romantic revenge research has received less attention than other interpersonal relationship contexts (e.g. the workplace).